Forms of citizenship in pre-modern South India. Issue 3 (3rd April 2019) - Washbrook, David
ABSTRACT: Citizenship has generally been associated with institutions located firmly in the political history of 'the West'. The state and governance in Asia, by contrast, are taken to have been dominated by 'Oriental' despotism and/or theocracy. As a result, citizenship in modern Asia may be alien, artificial and weakly rooted. Focusing closely on southern and western India, this paper challenges this perspective. Its argument centres on the existence from 'medieval' times of a series of institutions which, though certainly different from those in 'the West', performed many of the same 'citizen-like' functions. These functions were threatened by the rise of the early modern and colonial states, with their stronger traditions of bureaucracy and centralisation, but never entirely overcome. Their shadow continues to pattern India's practices of citizenship today, giving it many of its distinctive characteristics.